Health Promotion of Haitian immigrant families: possibilities and barriers in everyday life in Primary Care - Daniela Priscila Oliveira do Vale Tafner; Rosane Gonçalves Nitschke; Adriana Dutra Tholl; Ivonete Teresinha Schulter Buss Heidemann; Maria Lígia dos Reis Bellaguarda; Sonia Silva Marcon (Universidade Federal do Ceará, 2023)
Objective: to understand the possibilities and barriers in the everyday lives of primary care professionals for health promotion of Haitian immigrant families. Methods: qualitative interpretative research, based on the theoretical foundations of Comprehensive Sociology and Everyday life Sociology. Twenty-seven Primary Health Care professionals who assist Haitian immigrant families participated. Data were collected using an electronic form in Google Forms and submitted to Thematic Analysis. Results: three categories emerged: Public policies and specific actions; Potentialities in health promotion to Haitian families; and Professional everyday life and limitations to health promotion. Conclusion: professionals perceive that their professional everyday lives have the potential to promote the health of Haitian immigrant families. However, they recognize the limits related to language barriers, political conception, and social organization. To overcome these limits, it is believed necessary to strengthen existing policies and promote changes in the organization of services. Contributions to practice: the understanding of the potentials and limits will enable managers and professionals to reflect not only on changes in the work process, but also on changes in the everyday work, implementing effective strategies for Health Promotion.